The Influence of Sociodemographics and Maternal Parenting Patterns on the Incidence of Stunting in Toddlers Aged 6-23 Months - Tanjung, Maya Sari (International Journal of Medicine And publich Health, 2025)
Stunting (dwarfism) is a condition in which a toddler has a length or height that is less than minus two standard deviations of the median of the WHO child growth standards. Stunting is caused by insufficient nutritional intake over a long period of time due to feeding that does not meet nutritional needs. Stunting can occur from when the fetus is still in the womb and only becomes apparent when the child is two years old. This type of research is quantitative with a case-control study design, which is an analytical study (survey) concerning how risk factors are studied using a retrospective approach. The case population in this study were all stunted children aged 6-23 months in the Mompang Community Health Center working area. The control population in this study were non-stunted children aged 6-23 months in the North Panyabungan Community Health Center area who lived side by side with stunted children. The sampling technique for this study was accidental sampling, namely a method of sampling by chance encounter. The findings obtained by the researchers are largely supported by the results of previous studies that stated there is a relationship between sociodemographics and maternal parenting patterns on the incidence of stunting. Parents' education and income are important factors in fulfilling toddlers' nutritional needs, and parental parenting patterns are also supporting factors in providing care for better toddler growth and development.